PENERAPAN STRETEGI PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR MENGGAMBAR ORNAMEN SISWA KELAS X KOMPETENSI KEAHLIAN DESAIN DAN PRODUKSI KRIYA TEKSTIL SMK NEGERI 1 SUKASADA TAHUN PELAJARAN 2011-2012 - Murni, Ni Made (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2014)
This study was conducted in an effort to improve student learning outcomes in drawing ornaments through the implementation of inquiry learning strategy in class X Competency Design and Production of Textile Craft in the second semester of the academic year 2011/2012. This research is a classroom action research conducted in two cycles. Research results that the acquisition value of ornament drawing class X Competency Design and Textile Craft Production in the first cycle, 30% of the number of students has not reached the minimum completeness criteria (KKM) subjects is 70. The average value of drawing ornaments in the first cycle is 70. 4. In the second cycle of 100% of the number of students has reached KKM subjects and the average value was 85.0. The steps taken in the implementation of inquiry learning strategy is the direct observation of flora and fauna, was explored in the form of sketches. Sketch observations then distillation or deformed arranged in a particular composition to form an image of the observation ornamen.Sketsa distillation or deformed, and then arranged in a particular composition to be an ornament image. With the increased activity of observing and practicing, students can enhance creativity in automatic learning leads to student learning outcomes. This is caused by the characteristics of inquiry learning strategy that is oriented learning process of searching for and finding an integrated create opportunities and requires students to be active in learning. The natural learning process, students work and experience, so that the learning is more meaningful because it touches directly the needs of students.Keywords: strategy inquiry, learning.